Interplaying role of healthcare activist and homemaker: a mixed-methods exploration of the workload of community health workers (Accredited Social Health Activists) in India - Anand Kawade; Manisha Gore; Pallavi Lele; Uddhavi Chavan; Hilary Pinnock; Pam Smith; Sanjay Juvekar; for the RESPIRE collaboration (BMC, 2021)
Abstract Background Globally, community health workers (CHWs) are integral contributors to many health systems. In India, Accredited Social Health Activists (ASHAs) have been deployed since 2005. Engaged in multiple health care activities, they are a key link between the health system and population. ASHAs are expected to participate in new health programmes prompting interest in their current workload from the perspective of the health system, community and their family. Methods This mixed-methods design study was conducted in rural and tribal Primary Health Centers (PHCs), in Pune district, Western Maharashtra, India. All ASHAs affiliated with these PHCs were invited to participate in the quantitative study, those agreeing to contribute in-depth interviews (IDI) were enrolled in an additional qualitative study. Key informants' interviews were conducted with the Auxiliary Nurse Midwife (ANM), Block Facilitators (BFF) and Medical Officers (MO) of the same PHCs. Quantitative data were analysed using descriptive statistics. Qualitative data were analysed thematically. Results We recruited 67 ASHAs from the two PHCs. ASHAs worked up to 20 h/week in their village of residence, serving populations of approximately 800-1200, embracing an increasing range of activities, despite a workload that contributed to feelings of being rushed and tiredness. They juggled household work, other paid jobs and their ASHA activities. Practical problems with travel added to time involved, especially in tribal areas where transport is lacking. Their sense of benefiting the community coupled with respect and recognition gained in village brought happiness and job satisfaction. They were willing to take on new tasks. ASHAs perceived themselves as 'voluntary community health workers' rather than as 'health activists". Conclusions ASHAs were struggling to balance their significant ASHA work and domestic tasks. They were proud of their role as CHWs and willing to take on new activities. Strategies to recruit, train, skills enhancement, incentivise, and retain ASHAs, need to be prioritised. Evolving attitudes to the advantages/disadvantages of current voluntary status and role of ASHAs need to be understood and addressed if ASHAs are to be remain a key component in achieving universal health coverage in India.